1996
DOI: 10.1029/96rs02190
|View full text |Cite
|
Sign up to set email alerts
|

The measurement of gravity wave momentum flux in the lower atmosphere using VHF radar

Abstract: Radar measurements have often been used to estimate gravity wave momentum flux profiles in the troposphere, lower stratosphere, and mesosphere. The reliability of the measurements in the troposphere and lower stratosphere is investigated, with a comparison of three techniques employing various radar beam directions and zenith angles, including the standard "symmetric-beam" method. The study uses the 46.5 MHz MST radar system at Aberystwyth, Wales (52.4øN, 4.1øW). For short-period waves, errors in momentum flux… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 55 publications
2
39
0
Order By: Relevance
“…It is noticed that the magnitude and pattern of the momentum flux value, in general, is comparable to the results of early radar and non-radar studies of vertical flux (Fukao et al, 1988;McAfee et al, 1989;Sato, 1989;Worthington et al, 1996;Alexander and Pfister, 1995;Chang et al, 1997). In general, the momentum flux pattern and its general characteristics observed in the present work are similar to that of the observations mentioned above.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…It is noticed that the magnitude and pattern of the momentum flux value, in general, is comparable to the results of early radar and non-radar studies of vertical flux (Fukao et al, 1988;McAfee et al, 1989;Sato, 1989;Worthington et al, 1996;Alexander and Pfister, 1995;Chang et al, 1997). In general, the momentum flux pattern and its general characteristics observed in the present work are similar to that of the observations mentioned above.…”
Section: Resultssupporting
confidence: 80%
“…They found that variations in zonal momentum flux seem to show good correlation with shear and mean zonal wind each day and thereby suggested that day-to-day variations of gravity waves are caused by variations of wind shear. Vertical flux of horizontal momentum in the troposphere and lower stratosphere have been studied by Prichard and Thomas (1993) and Worthington and Thomas (1996) using MST radar at Aberystwyth. They found that momentum fluxes for long period waves show little changes with activity, whereas momentum flux values of shorter periods are enhanced substantially during active periods.…”
Section: Introductionmentioning
confidence: 99%
“…Kelvin-Helmholtz instability offers an useful conceptual model [Worthington and Thomas, 1996;Muschinski, 1996 The agreement between the azimuth of tilted layers found using Gaussian moments (with tilt angles <1ø), and using power imbalances (apparently much larger tilts) shows they are closely related, both to If the existence of large power imbalances between symmetric off-vertical beams is inconsistent with a simple tilt of <1 ø (section 3), it may be the case that AOA measurements using SI must be performed for each beam pointing direction individually. In other words, it may be impossible to define a single AOA which indicates the effect of tilted layers on both vertical and off-vertical beams, and also not possible for DBS systems to measure vertical-beam AOA.…”
Section: Discussionmentioning
confidence: 99%
“…Pro®les based on 1-h sections of the horizontal wind, power di erence, and echo power data, using various beams, are plotted in Figs Worthington and Thomas (1996b) in connection with the possible e ects of tilted layers on velocity and momentum¯ux measurements. Standard errors on the pro®les of velocities, power di erences, and powers are less than 0.5 m s À1 , 1.3 dB and 0.9 dB respectively.…”
Section: Observationsmentioning
confidence: 99%